Development of an in vitro skin model - Škrinjar, Dominik; Sever, Maja; Maver, Tina; Gradišnik, Lidija; Zidarič, Tanja (Anali PAZU, 2024)
In this study, we developed bioink for 3D printing incorporating human skin cells, composed of alginate, methylcellulose, and nanofibrillar cellulose in a cell medium. The 3D bioprinter allows the creation of multilayer scaffolds that simulate the natural cellular microenvironment of the skin. Due to the need for reproducibility, we stored the bioink in a freezer and thawed it later. The rheological properties of the material after thawing significantly affect its viscosity, impacting the feasibility of 3D printing and the stability of the printed scaffolds. We found that the freezing temperature notably influences these properties, which is crucial for the further development of an in vitro skin model, promising for preclinical and clinical research.
Keywords: in vitro skin model; rheology; 3D printing; preclinical medicine; skin diseases